Professional learning community model in improving teachers’ pedagogical competence to face Alpha generation - Wardatina, Wardatina; Rasyid, Suparta; Ismail , Ismail; Nabila, Nudhar (Universitas Jambi, Indonesia, 2026)
This study examines how the Professional Learning Community (PLC) enhances teachers’ pedagogical competence in addressing the learning characteristics of Generation Alpha. Employing a qualitative case study design, the research was conducted in two vocational schools in Aceh Jaya involving 13 participants, including principals, teachers, and a supervisor. Data were collected through in-depth interviews, participatory observation, and documentation and analyzed using thematic analysis with triangulation to ensure trustworthiness. The findings reveal that PLC fosters collaborative learning, reflective practice, and technology integration, which contribute to improved instructional strategies, digital literacy, and teacher confidence. Furthermore, PLC transforms professional practices from administrative routines into continuous, reflective, and student-centered learning processes. This study highlights PLC as an effective and sustainable model for strengthening pedagogical competence and supporting educational transformation in the context of Society 5.0.